Longitudinal neurological analysis of moderate and severe pediatric cerebral visual impairment - Jimenez-Gomez, Andres; Fisher, Kristen S.; Zhang, Kevin X.; Liu, Chunyan; Sun, Qin; Shah, Veeral S. (Frontiers in Human Neuroscience, 2022)
Introduction: Cerebral visual impairment (CVI) results from damage to cerebral visual processing structures. There is currently limited understanding on how neurologic, developmental, and ophthalmic factors predict outcome for pediatric CVI. Method: A retrospective manual chart review of pediatric CVI patients seen at a tertiary pediatric hospital between 2010-2019 was conducted. Patients were stratified into severity groups (based on a custom CVI grading score). Collected baseline characteristics included perinatal, genetic, developmental and neurologic history, neuroimaging and fundoscopic findings. Longitudinal data were collected and a linear mixed-effect models were used for CVI outcome analysis. Results: 249 individuals spanning 779 patient visits were identified. Mean age at diagnosis was 18.8 ± 16.8 months (2-108 months). 64.3% were born at term age. Perinatal history revealed hypoxic ischemic encephalopathy (HIE) in 16.5%, intraventricular hemorrhage (IVH) in 11.6%, and seizures in 21.7%. At presentation, 60.3% had a diagnosis of cerebral palsy and 84.7% had developmental delay. Among all subjects, 78.6% had epilepsy; 33.8% had an epileptic encephalopathy. Abnormal neuroimaging was present in 93.8%. Genetic anomalies were present in 26.9%. Baseline visual examination revealed no blink-to-light (BTL) in 24.5%; only BTL in 34.5%, fixation/tracking in 26.5%, and optokinetic drum follow in 14.4%. Longitudinal data analysis showed that perinatal history of HIE, a positive epilepsy history, multiple (≥3) epilepsy medications, cerebral palsy, and abnormal fundoscopic findings were all negatively associated with CVI grade change over time. After controlling for significant confounders, receiving any type of therapy (early childhood intervention [ECI], physical and occupational therapy [PT/OT], refractive error correction or glasses) was significantly associated with longitudinal improvement in CVI grade compared to patients who did not receive any therapy. Conclusions: This study offers extensive insights into neurologic, developmental and ophthalmologic features in patients with moderate to severe CVI. Aspects of perinatal history and epilepsy/seizure control may help inform severity/prognosis in the general neurology or ophthalmology clinic. Moreover, genetic and specific epilepsy traits may alert vision health care providers in the clinic to pursue visual evaluation in at-risk individuals. Longitudinal follow-up of CVI patients showed that interventional therapies demonstrated vision function improvement greater than no therapy and maturational development.